MILLING OF TITANIUM ALLOY USING HEXAGONAL BORON NITRIDE (hBN) NANOFLUID AS A COOLANT - Liew, P.J.; Maisarah, K.O.; Juoi, J.M.; Wang, J. (Journal of Advanced Manufacturing Technology (JAMT), 2019)
Titanium has been used for many areas, such as aircraft turbine blade, fuel tanks, marine hardware and surgical implant. Due to its high hardness and high temperature when machining, the conventional method such as dry machining leads to rough surface roughness, high cutting force and short tool life. This study aims to evaluate the effect of different concentrations of hexagonal boron nitride (hBN) nanofluid on the cutting force, tool wear and surface roughness of titanium alloy using milling process. In this research, three different concentrations, namely 0.02, 0.06 and 0.1 wt% of hBN nanofluid were used, and their performance was compared with that of pure deionised (DI) water. The nanofluid was prepared by mixing the hBN nanoparticles with DI water and polyvinylpyrrolidone K30 as surfactant. The experimental results indicate that the machining performance of titanium alloy is better by using hBN nanofluid than by using pure DI water. Cutting force, tool wear and surface roughness are approximately reduced by 16.1%, 63.9% and 33.3% respectively by using 0.1wt% of hBN nanofluid compared to pure deionised water.